PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BIOLOGI MATERI STRUKTUR DAN FUNGSI SEL DI SMAN 1 TELUK KERAMAT - Purnamasari, Indah; Fadillah, Fadillah; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThis study aims to produce media products in the form of multimedia learning. The development model used is a 4-D model (four D models) by limiting it to only 3 stages namely the stage of defining the design and development. Data collection techniques are observation, interviews, and measurement techniques with data collection tools namely observation sheets, interview guides, questionnaires and test results for learning outcomes. Before conducting research, multimedia learning biology material structure and cell function in SMA Negeri 1 Teluk Keramat was validated by material experts 94.17% with very valid categories, media experts 80.01% with very valid criteria and 81.25% design experts with very valid criteria and field trials that show a positive response to the use of multimedia learning by 85.95% with very positive criteria. The results showed that the learning outcomes of students before using multimedia learning is 65.67 and after using multimedia learning is 81.67 with a good category.Â Keywords: Multimedia Learning Biology Material Structure and Cell Function, 4D model